Religion in 50 words: a critical vocabulary - Hughes, Aaron W. (Routledge, Taylor & Francis, 2022)
"Religion in 50 Words: A Critical Vocabulary is the first of a two-volume work that seeks to transform the study of religion by offering a radically critical perspective. It does so by providing a succinct and critical examination of the key words used in the modern study of religion. Arranged alphabetically, the book explores the historic roots, varied uses, and current significance and utility of the technical terms used within the current field of religious studies. These are the terms that both students and scholars routinely deploy to think about, describe, and analyze data-sometimes without realizing that they are themselves technical tools in need of attention. Among the topics covered: Belief Culture Critical Definition Environment Gender Ideology Lived Religion Material Religion Politics Orthodoxy Race Sacred/Profane Secular Theory This book submits all of its terms to a critical interrogation and subsequent re-description, thereby allowing a collective reframing of the field. This volume is an indispensable resource for students and academics working in religious studies"--